1984
DOI: 10.1243/emed_jour_1984_013_022_02
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Broadband Ultrasonic Attenuation in Cancellous Bone

Abstract: We have carried out measurements of the frequency dependence of ultrasonic attenuation in the range 0.2-1 MHz in in vitro samples of bovine cancellous bone and in vivo 0s calcis heel bones. A comparison of the results allows us to infer that the in vivo measurements are dependent on the bone mineral content of the 0s calcis. The bone mineral content has been determined in this way for three female populations and indicates that the technique allows determination of bone loss and the study of the onset and prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
268
0
13

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 629 publications
(284 citation statements)
references
References 8 publications
(4 reference statements)
3
268
0
13
Order By: Relevance
“…Langton et al 7) showed that, when ultrasound is transmitted through a certain object, its amplitude diminishes due to scattering and absorption, and this effect depends on the frequency of the ultrasound transmitted and the strength of the object. They stated that the attenuation property could be represented as BUA by performing a Fourier transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Langton et al 7) showed that, when ultrasound is transmitted through a certain object, its amplitude diminishes due to scattering and absorption, and this effect depends on the frequency of the ultrasound transmitted and the strength of the object. They stated that the attenuation property could be represented as BUA by performing a Fourier transformation.…”
Section: Discussionmentioning
confidence: 99%
“…1,10,27,[39][40][41][42][43][44][45] Some of the earliest strongest evidence to support the use of QUS for discriminating between osteoporotic fractures and controls has come from large prospective studies. The first of these was published in 1990, when Porter et al measured 1 414 women over the age of 69 who were in residential accommodation.…”
Section: Fracture Discriminationmentioning
confidence: 99%
“…1 The calcaneus was chosen as a site for measurement since it is easily accessible, with the medial and lateral aspects being relatively flat and parallel. It contains approximately 90% trabecular bone, which has a high metabolic turnover rate and a pattern of bone loss similar to the spine.…”
mentioning
confidence: 99%
“…Ultrasound based densitometry is considered as a cheap, ionizing radiation free and easy to use alternative indicator of skeletal status in the trabecular bone of the calcareous. 12 Osteoporosis in COPD patients is often underdiagnosed. 13 Smoking has been shown to be an independent risk factor for osteoporosis among both genders.…”
Section: Introductionmentioning
confidence: 99%